Engineering flame and mechanical properties of natural plant-based fibre biocomposites - Mojtaba Ahmadi; Omid Zabihi; Zahra Komeily Nia; Vishnu Unnikrishnan; Colin J. Barrow; Minoo Naebe (Advanced Industrial and Engineering Polymer Research)
The escalating global concerns surrounding unsustainable petroleum consumption have fueled interest in natural plant fiber polymer biocomposites (NFPCs) as eco-friendly alternatives. NFPCs offer advantages such as low density, specific mechanical properties, recyclability, and biodegradability. Despite their potential for addressing environmental issues and serving as cost-effective alternatives for per- and polyfluoroalkyl substances (PFAS) remediation, challenges exist due to their poor thermal stability and flammability. This comprehensive review delves into efforts to enhance the flame resistance of NFPCs, focusing on flammability testing methods, the impact of flame retardants, and underlying flammability mechanisms. Emphasizing the delicate balance between flame resistance and structural integrity, the review establishes a framework for understanding the thermo-structural response of burning NFPCs. Additionally, it explores sustainability and recycling aspects, offering insights crucial for comprehending fire-induced damage processes in NFPCs, especially in high-performance applications where exposure to high temperatures is inevitable.